Effect Of The Combined Addition Of Brick Waste Powder And Dune Sand Powder On The Mechanical Performance Of A Lime-Treated Gypsiferous Tuff - Cherif Baiker, Mohamed; Abderrezak Khellou; Saïd Abani (International Journal of Computational and Experimental Science and Engineering, 2026)
This study investigates the improvement of mechanical performance and water durability of a gypsiferous tuff from southeastern Algeria, with the aim of its application in road infrastructure. The natural material, characterized by low cohesion and high water sensitivity, was treated through the combined addition of lime, finely ground brick waste powder, and dune sand powder. Several mix formulations were developed to assess the individual and synergistic effects of these additions on the mechanical behavior of the tuff. The experimental program included unconfined compressive strength, indirect tensile strength, water sensitivity, durability under wetting–drying cycles, and direct shear strength parameters. The results indicate that lime treatment significantly enhances material cohesion, while the incorporation of brick waste powder leads to a substantial mechanical gain attributed to the development of pozzolanic reactions. The contribution of dune sand powder is mainly associated with a granular densification effect, resulting in an improvement of the internal friction angle and overall structural stability. Microstructural analysis using scanning electron microscopy corroborates these macroscopic findings by revealing the formation of secondary cementitious products and a marked reduction in porosity for the most efficient mixtures.